Phytochemical studies and antibacterial activity of the aerial parts of Physospermum verticillatum - Ibtissem Boulacel; Lakhdar Djarri; Salima Azzouzi; Kamel Medjroubi; Ibrahim Demirtas; Hocine Laouer; Salah Akkal (Bangladesh Pharmacological Society, 2017)
In this study, we focused on the isolation and identification of the main compounds, triterpene, sterol, phenolic and fatty acid from the aerial parts of Physospermum verticillatum, which has not been previously reported. Dichloromethane, ethyl acetate and n-butanol extracts led to the isolation  of ß-amyrin (1), 3,11-dihydroxy-12-oleanene (2), pentadecanoic acid (3), spina-sterol (4), spinasterol-3-O-ß-D-glucopyranoside (5) and saikochromic acid (6). These compounds were determined by means of the combined systems with high resolution tandem mass spectrometry (HPLC-TOF/MS), 1D NMR (1H NMR, 13C NMR) and 2D NMR(COSY, HSQC and HMBC). Further, the extracts demonstrated significant antibacterial activity.